The Patriot (Columbia Pictures Industries, 2000)
In 1776 South Carolina, widower Benjamin Martin (Gibson) finds himself thrust into the midst of the American Revolutionary war as he helplessly watches his family being torn apart by the savage forces of the British Recoats. when his oldest son's wife is ruthlessly killed, and his own eyes, Martin is no longer able to suppress the soldier within that he tried to bury with his own military past. Unable to remain silent he recruits a band of unlikely volunteers to take up arms against the British. Fighting to protect his family's freedom and his country's independence, Martin discovers the pain of betrayal, the redemption of revenge and the passion of love.